2018
DOI: 10.12962/j23373539.v7i1.28908
|View full text |Cite
|
Sign up to set email alerts
|

Pemodelan Spasial Genangan Banjir Akibat Gelombang Pasang di Wilayah Pesisir Kota Mataram

Abstract: C 33 Abstrak-Dampak kenaikan muka air laut di Kota Mataram menyebabkan 6 (enam) Kelurahan di 2 (dua) Kecamatan terdampak banjir tiap tahunnya. Untuk mencegah kerusakan yang lebih parah, solusi yang dapat dilakukan adalah membuat pemodelan wilayah terdampak banjir sebagai acuan dalam perencanaan pembangunan kedepannya. Pada bulan Januari 2017, gelombang pasang merendam 1.161 rumah warga di tujuh kelurahan mencakup dua kecamatan, yakni Ampenan dan Sekarbela. Di Ampenan ada empat kelurahan yang terkena dampaknya,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
1
3
0
2
Order By: Relevance
“…[20] concluded that river discharge was largely responsible for flooding along the river and the river mouth. The [18] study supports that a tidal wave would cause higher flooding along the river mouth of the Ampenan and the Sekarbela subdistricts. Thus, it can be said that the CFR-new value was lower because the high-vulnerability classes of the CFC had a strong relationship with the river mouth.…”
Section: Evaluation Of the Cfr-new And Cfc Methodssupporting
confidence: 66%
See 3 more Smart Citations
“…[20] concluded that river discharge was largely responsible for flooding along the river and the river mouth. The [18] study supports that a tidal wave would cause higher flooding along the river mouth of the Ampenan and the Sekarbela subdistricts. Thus, it can be said that the CFR-new value was lower because the high-vulnerability classes of the CFC had a strong relationship with the river mouth.…”
Section: Evaluation Of the Cfr-new And Cfc Methodssupporting
confidence: 66%
“…The two rivers that have the impact of flooding emptying into the coast of Mataram are the Jangkik River and the Unus River. Mataram City is inundated every year, and the impact is exacerbated during monsoons [18]. Tidal waves are the major factor that caused inundation in the coastal city of Mataram [19][20][21].…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…Wilayah darat daerah pesisir masih dipengaruhi pasang surut, badai dari laut dan tidak sedikit mengalami intrusi air laut (Zulaykha et al, 2015). Daerah pesisir di Indonesia, merupakan daerah yang cukup berkembang, dua pertiga kota-kota di Indonesia masuk pada kategori wilayah pesisir dan jumlah penduduk Indonesia yang bermukim di wilayah pesisir diperkirakan lebih dari 60% total penduduk Indonesia (Rahmanto and Susetyo, 2018). Salah satu kota pesisir di Indonesia Kota Tarakan.…”
unclassified